Drude's model calculation rule on electrical transport in Sb-doped SnO2 thin films, deposited via sol-gel - Geraldo, Viviany; Scalvi, Luis Vicente de Andrade [UNESP]; Lisboa Filho, Paulo Noronha [UNESP]; Morilla-Santos, C. (Elsevier B.V., 2006)
The evaluation of free carrier concentration based on Drude's theory can be performed by the use of optical transmittance in the range 800-2000 nm (near infrared) for Sb-doped SnO2 thin films. In this article, we estimate the free carrier concentration for these films, which are deposited via sol-gel dip-coating. At approximately 900 mn, there is a separation among transmittance curves of doped and undoped samples. The plasma resonance phenomena approach leads to free carrier concentration of about 5 x 1020 cm(-3). The increase in the Sb concentration increases the film conductivity; however, the magnitude of measured resistivity is still very high. The only way to combine such a high free carrier concentration with a rather low conductivity is to have a very low mobility. It becomes possible when the crystallite dimensions are taken into account. We obtain grains with 5 nm of average size by estimating the grain size from X-ray diffraction data, and by using line broadening in the diffraction pattern. The low conductivity is due to very intense scattering at the grain boundary, which is created by the presence of a large amount of nanoscopic crystallites. Such a result is in accordance with X-ray photoemission spectroscopy data that pointed to Sb incorporation proportional to the free electron concentration, evaluated according to Drude's model. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: oxides; semiconductors; sol-gel growth; transport properties